The A-Z of Payments : A Modern and Practical Glossary for the Curious and the Forgetful - Jones, Neira (Routledge, 2025)
With over 1,600 entries, The A-Z of Payments provides readers with a comprehensive, practical, easy-to-read listing of payment terms. The financial services industry is full of terms and abbreviations that can appear confusing or easy to forget (e.g. ACS, 3DS, RTP, PCI DSS, POS, PoS, A2A, P2P, and BaaS). This handy glossary, written in a plain and accessiblestyle, is the perfect desktop companion for experienced practitioners wanting to keep a check on the latest terminology, fintech students starting outwhowant to navigate the world of payments quickly, or those curious about terminology. It will also appeal to those wanting to understand terms related to parts of the industry with which they are unfamiliar, whilst those new to the industry will use it as a reference to understand documentation they access, or better equip them for conversations they might have. The A-Z of Payments is the ideal companion to anyone undertaking training in payments or on finance courses. It is particularly relevant to private sector corporations, regulators, and their employees.